Comparative Analysis of Wind Load Standards on Space Truss Structures: Analisis Perbandingan Standar Beban Angin pada Struktur Rangka Ruang - Mahesha Gani Tarigan; Johannes Tarigan; Nursyamsi Nursyamsi (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Structural design requires precise determination of loading, with wind load being a critical component that influences the safety and behavior of buildings. Specific Background: In Indonesia, wind load regulations have evolved significantly—from PPIUG 1983 to SNI 1727:2013 and the latest SNI 1727:2020—reflecting changes in building practices and meteorological understanding. Knowledge Gap: However, the comparative impact of these evolving standards on spatial truss structures remains insufficiently explored. Aims: This study investigates how the three standards affect wind load distribution and structural response in space trusses using ETABS software. Results: Findings reveal substantial differences, with SNI 1727:2020 producing the highest mid-span wind pressure (0.886 kN/m²), exceeding that of SNI 1727:2013 (0.546 kN/m²), due to the introduction of the elevation coefficient (Ke) and revisions in building categorization. Novelty: This research uniquely highlights how regulatory evolution introduces quantifiable changes in displacement, axial force behavior, and total structural weight. Implications: The study informs engineers and designers of the critical implications of standard selection, promoting better-informed structural safety and optimization decisions in modern Indonesian construction. Highlights: Highlights regulatory evolution from PPIUG 1983 to SNI 1727:2020. Shows impact of new wind pressure coefficient (Ke) on design results. Compares structural responses under different wind load standards. Keywords: Wind Load, Space Truss, Structural Analysis, Indonesian Standards, ETABS